2022
DOI: 10.1186/s12943-022-01582-0
|View full text |Cite
|
Sign up to set email alerts
|

The functional roles of the circRNA/Wnt axis in cancer

Abstract: CircRNAs, covalently closed noncoding RNAs, are widely expressed in a wide range of species ranging from viruses to plants to mammals. CircRNAs were enriched in the Wnt pathway. Aberrant Wnt pathway activation is involved in the development of various types of cancers. Accumulating evidence indicates that the circRNA/Wnt axis modulates the expression of cancer-associated genes and then regulates cancer progression. Wnt pathway-related circRNA expression is obviously associated with many clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 321 publications
0
40
0
Order By: Relevance
“…Circular RNA (circRNA), an endogenous noncoding RNA with a covalently closed-loop structure but without a 5′ cap and 3′ polyadenylate tail, is resistant to exonucleases [ 7 ]. A large number of previous studies have confirmed the presence of circRNAs in a variety of diseases and cancers [ 8 ]. Some reports revealed the involvement and different roles of many circRNAs in the development of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA (circRNA), an endogenous noncoding RNA with a covalently closed-loop structure but without a 5′ cap and 3′ polyadenylate tail, is resistant to exonucleases [ 7 ]. A large number of previous studies have confirmed the presence of circRNAs in a variety of diseases and cancers [ 8 ]. Some reports revealed the involvement and different roles of many circRNAs in the development of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been a large amount of studies on circular RNAs, and now we have better understanding of the roles of circular RNAs in biogenesis and biology. However, the regulatory functions and corresponding mechanisms in many diseases, especially tumors, are still not thoroughly studied [41][42][43][44][45][46]. At present, there are relatively few reports on the development, metastasis and drug resistance of circRNAs in ESCC, and the specific mechanism needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…circRNA is a new type of noncoding RNA member composed of one or more spliced exons or introns, which has the characteristics of conservation, richness, and tissue specificity, so it may play a special molecular marker role in some diseases (such as tumors) [25]. circRNA can regulate gene expression by alternative splicing, regulating the expression of parental genes, and acting as a scaffold for protein complex assembly and RNA protein interaction and affect the occurrence and development of tumors [26,27].…”
Section: Discussionmentioning
confidence: 99%